Three-component microwave-assisted synthesis of 3,5-disubstituted pyrazolo[3,4-d]pyrimidin-4-ones - Ng, Jia Hui; Tiekink, Edward R. T.*; Dolzhenko, Anton V. (Royal Society of Chemistry, 2022)
A practical three-component method for the synthesis of pyrazolo[3,4-d]pyrimidin-4-ones was developed. The reaction was performed in a one-pot manner under controlled microwave irradiation using easily accessible methyl 5-aminopyrazole-4-carboxylates, trimethyl orthoformate, and primary amines. Under the optimized conditions, challenging substrates, such as N-1 unsubstituted 5-aminopyrazole-4-carboxylates with another substituted amino group in position 3, reacted selectively affording 5-substituted 3-arylamino-1,5-dihydro-4H-pyrazolo[3,4-d]pyrimidin-4-ones. The reaction tolerated a range of primary amines, including anilines. The advantages of the developed protocol include short reaction time, pot- and step-economy, and convenient chromatography-free product isolation. The structural features of representative products were explored by X-ray crystallography